Italica: municipium civium romanorum - Fear, A. T. (Florentia Iliberritana, 2016)
This article surveys the theories concerning the legal status of the town of Italica prior to its being raised to the rank of a colonia C. R. The conclusion drawn is that despite recent theories to the contrary, the traditional view thwt Italica he id the rank of a municipium civium Romanorum during this period is the correct one. This is followed by a discussion · of the provenance and nature of a fragment of a municipal law discovered in the last century possibly at Italica.